Percutaneous Transabdominal Approach for the Treatment of Endoleaks after Endovascular Repair of Infrarenal Abdominal Aortic Aneurysm - Choi, Sun Young (The Korean Society of Radiology, 2010)
OBJECTIVE: The purpose of this study was to evaluate the technical feasibility and clinical efficacy of percutaneous transabdominal treatment of endoleaks after endovascular aneurysm repair. MATERIALS AND METHODS: Between 2000 and 2007, six patients with type I (n = 4) or II (n = 2) endoleaks were treated by the percutaneous transabdominal approach using embolization with N-butyl cyanoacrylate with or without coils. Five patients underwent a single session and one patient had two sessions of embolization. The median time between aneurysm repair and endoleak treatment was 25.5 months (range: 0-84 months). Follow-up CT images were evaluated for changes in the size and shape of the aneurysm sac and presence or resolution of endoleaks. The median follow-up after endoleak treatment was 16.4 months (range: 0-37 months) RESULTS: Technical success was achieved in all six patients. Clinical success was achieved in four patients with complete resolution of the endoleak confirmed by follow-up CT. Clinical failure was observed in two patients. One eventually underwent surgical conversion, and the other was lost to follow-up. There were no procedure-related complications. CONCLUSION: The percutaneous transabdominal approach for the treatment of type I or II endoleaks, after endovascular aneurysm repair, is an alternative method when conventional endovascular methods have failed.